2017
DOI: 10.1111/apa.13738
|View full text |Cite
|
Sign up to set email alerts
|

How to create a successful reader? Milestones in reading development from birth to adolescence

Abstract: Reading is one of the most important academic abilities that establishes the foundation for a child's success in school. Therefore, early and accurate diagnosis of reading challenges is crucial for prevention of later academic failure. One challenge in early detection of reading difficulties is that the ability to read typically is acquired explicitly when a child is four to six years of age. However, reading ability relies on development of more basic abilities prior to reading acquisition, starting from birt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
36
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 48 publications
0
36
0
Order By: Relevance
“…They are obtaining information on neural processes related to actual reading processes, 25 and the accompanying skills and attitudes which develop; for example fluent reading was found to be supported by executive function areas. (See Horowitz-Kraus and Hutton 2015, Horowitz-Kraus et al 2017.…”
Section: 7mentioning
confidence: 99%
“…They are obtaining information on neural processes related to actual reading processes, 25 and the accompanying skills and attitudes which develop; for example fluent reading was found to be supported by executive function areas. (See Horowitz-Kraus and Hutton 2015, Horowitz-Kraus et al 2017.…”
Section: 7mentioning
confidence: 99%
“…In the general population in Europe and the US, 5–12% of all children have reading difficulties (Horowitz-Kraus et al. 2017 ), with boys more often affected than girls (Hawke et al. 2009 , Yoshimasu et al .…”
Section: Reading Difficulties and Mental Health Problems In The General Populationmentioning
confidence: 99%
“…In support of the lexical quality model it has been shown that word decoding and vocabulary jointly predicts the development of reading comprehension in the general population (e.g. Horowitz-Kraus et al 2017, Verhoeven et al 2011.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“… Hutton et al (2015) conducted a neuroimaging study that found that greater parent–child shared book reading increased the activation of left parietal–temporal–occipital areas supporting mental imagery and narrative comprehension. Successive studies further attribute the acceleration of children’s picture-book reading to higher cognitive brain network construction ( Horowitz-Kraus et al, 2017 ; Hutton et al, 2017a , b ). On the other hand, advances in multimedia technologies in the digital age are changing the ways in which children learn a language ( Vulchanova et al, 2017 ), with various apps on a range of portable platforms enriching children’s ubiquitous access to story sharing and multilingual learning ( Parish-Morris et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%